QUALITY ASSESSMENT OF ETHICS ANALYSES FOR HEALTH TECHNOLOGY ASSSESSMENT. (5th December 2016) - Scott, Anna Mae; Bond, Kenneth; Gutiérrez-Ibarluzea, Iñaki; Hofmann, Björn; Sandman, Lars
Abstract : Objectives: Although consideration of ethical issues is recognized as a crucial part of health technology assessment, ethics analysis for HTA is generally perceived as methodologically underdeveloped in comparison to other HTA domains. The aim of our study is (i) to verify existing tools for quality assessment of ethics analyses for HTA, (ii) to consider some arguments for and against the need for quality assessment tools for ethics analyses for HTA, and (iii) to propose a preliminary set of criteria that could be used for assessing the quality of ethics analyses for HTA. Methods: We systematically reviewed the literature, reviewed HTA organizations' Web sites, and solicited views from thirty-two experts in the field of ethics for HTA. Results: The database and HTA agency Web site searches yielded 420 references (413 from databases, seven from HTA Web sites). No formal instruments for assessing the quality of ethics analyses for HTA purposes were identified. Thirty-two experts in the field of ethics for HTA from ten countries, who were brought together at two workshops held in Edmonton (Canada) and Cologne (Germany) confirmed the findings from the literature. Conclusions: Generating a quality assessment tool for ethics analyses in HTA would confer considerable benefits, including methodological alignment with other areas of HTA, increase in transparency and transferability of ethics analyses, and provision of common language between the various participants in the HTA process. We propose key characteristics of quality assessment tools for this purpose, which can be applied to ethics analyses for HTA purposes.